ANALISIS PENGARUH STRUCTURAL CAPITAL EFFICIENCY DAN CAPITAL EMPLOYED EFFICIENCY TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 - 2018 - Esti Damayanti, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This research was conducted with the aim of obtaining empirical evidence regarding how is the effect of structural capital efficiency and capital employed efficiency on the financial performance of the banking sector listed on the Stock Exchange Indonesia (IDX). This study took financial statement data for three periods, namely from 2016 to 2018 with a total sample of 14 companies. The sampling technique in this study was using purposive sampling and data processing techniques using multiple linear regression analysis processed through the SPSS program. The results obtained in this study indicate that Capital Employed Efficiency has a significant effect on financial performance and Structural Capital Efficiency has a significant effect on the company's financial performance.